2020
DOI: 10.1177/0890117120924176
|View full text |Cite
|
Sign up to set email alerts
|

A Focus Group Evaluation of Breathe Easier: A Mindfulness-Based mHealth App for Survivors of Lung Cancer and Their Family Members

Abstract: Purpose: To explore attitudes and acceptance (i.e., intent for future adoption) of survivors of lung cancer and their family members toward a dyad-focused mHealth mindfulness-based intervention (MBI). Approach: Focus groups. Setting: Community hospital setting in South Carolina. Participants: Survivors n = 11 (M = 64.6 years; 73% female; 64% African American) of non-small cell lung cancer (stage I-IIIa) and their family members, n = 8 (M = 58.6 years; 38% female; 75% African American). Intervention: A fully fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(77 citation statements)
references
References 26 publications
(30 reference statements)
0
74
1
1
Order By: Relevance
“…Dyadic interventions are described as holding great promise because they simultaneously target survivors, family members, and relationship factors that have an impact on health-related issues like symptom management and rehabilitation. 45,46 We found that some family members and friends were initially reluctant to participate but grew to value the experience as they realized the benefits to the survivor and, often unexpectedly, to themselves. Other studies recruiting survivors of lung cancer and partners found denial of the need for a support intervention to be the primary reason for refusing participation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dyadic interventions are described as holding great promise because they simultaneously target survivors, family members, and relationship factors that have an impact on health-related issues like symptom management and rehabilitation. 45,46 We found that some family members and friends were initially reluctant to participate but grew to value the experience as they realized the benefits to the survivor and, often unexpectedly, to themselves. Other studies recruiting survivors of lung cancer and partners found denial of the need for a support intervention to be the primary reason for refusing participation.…”
Section: Discussionmentioning
confidence: 97%
“…We developed and tested a mobile app prototype of this intervention that requires additional development and testing to maximize efficient delivery and potential widespread dissemination. 46,47…”
Section: Discussionmentioning
confidence: 99%
“…The other studies (1 focus group, 1 descriptive study, and 1 survey) included CAM as the primary topic. Beer et al’s study conducted 4 focus groups with 11 lung cancer survivors (64% African American) 18 and their family members. Hamilton et al’s qualitative descriptive study interviewed African Americans over age 50 who were survivors of any type of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 documents cross-sectional or qualitative studies (n = 6; 4 focus groups, 1 descriptive study, 1 cross-sectional survey-based study) that have examined the acceptability or use of CAM among AACS. Four of these descriptive studies included only AACS; 1 study included cancer survivors of various racial backgrounds (64%) identified as African American, 18 and one study included cancer survivors who were uninsured and of a minority background, with 98% identifying as African American. 17 …”
Section: Methodsmentioning
confidence: 99%
“…In the era of globalization and transformation of technology nowadays, challenges started to arise and most of them are in terms of the ageing population and runway healthcare cost. e-health offers the opportunities to both public as well as private healthcare providers [16] in optimizing its services besides upgrading the quality of service and care to patients. e-health is defined as the "use of information and communications technologies (ICT) in support of health and health-related fields, including health-care services, health surveillance, health literature, and health education, knowledge and research".…”
Section: Related Workmentioning
confidence: 99%